Thin-Film LSCs Based on PMMA Nanohybrid Coatings: Device Optimization and Outdoor Performance - S. M. El-Bashir; O. A. AlHarbi; M. S. AlSalhi (International Journal of Photoenergy)
This study concerns the design optimization of thin-film luminescent solar concentrators (TLSCs) based on polymethylmethacrylate (PMMA)/silica nanohybrid films doped with coumarin dyestuffs specialized in coloring plastics. Two designs of TLSCs had been prepared and characterized. The first consists of a transparent nanohybrid layer coated on a fluorescent PMMA substrate. The second design is the ordinary configuration in which fluorescent nanohybrid layer is coated on a transparent PMMA substrate. The investigation of the spectral properties and efficiency parameters recommended the best solar energy conversion efficiency for the second design. The outdoor performance of optimized TLSC was also evaluated under clear sky conditions of Riyadh city, and the hourly values of the optical efficiency, ηopt, were calculated for one year. The best performance was achieved in summer since the short circuit current for PV cell was doubled after being attached to TLSC and the value of ηopt reached 40% which is higher than other values recorded before due to the abundant solar energy potential in the Arabian Peninsula.